Study on Hematological and Biochemical Index of Blood and Vitreous Humor in the Celestial-Eye Goldfish - Rongni Li; Yansheng Sun; Xin Zhang; Wentong Li (Applied Sciences)
In this study, we conducted an exploration of blood collection, hematological and biochemical comparative analysis of the unique vitreous humor and blood of the celestial-eye goldfish (CE) (Carassius auratus), and obtained hematological and biochemical indicators for healthy celestial goldfish blood. After exploring the optimal method for collecting blood and ocular fluid, blood and vitreous humor samples were drawn from healthy CE, and an automatic hematology analyzer was used to measure 17 physiological indicators in the blood and vitreous humor. Additionally, 20 biochemical indices were measured by an automatic biochemical analyzer. Experiments were also conductedto evaluate the effect of blood and vitreous humor collection on the subsequent survival rate of the CE. The results showed that the blood of CE exhibited values for 17 hematological indicators, including red blood cells (mean value: 2.19 × 1012/L), white blood cells (mean value: 62.21 × 109/L), hemoglobin (mean value:138.25 g/L), and no eosinophils or basophils. We also found that the levels of aspartate amino transferase (AST) and glutamyl transpeptidase (GGT) in the vitreous humor of CE were significantly higher than those in the serum (p < 0.01). No cells were detected in the vitreous humor of CE, and there was no significant difference in survival rate compared to normal goldfish after extracting blood and vitreous humor from CE (p > 0.05). This study provides fundamental data for the cultivation of healthy goldfish, the development of goldfish hematology, and further research on the development and formation of CE’s unique eye traits.